PERFORMANCE IMPROVEMENT OF HYBRID RENEWABLE ENERGY SISTEM WITH SCHEDULING ENERGY DISTRIBUTION - HAEKAL BUDIMAN (NIM: 13313015) - MUHAMMAD AHSANUDDIN ABDURROHIM (NIM : 13313091), MUHAMMAD
Hybrid based elicticity use is growing, especially in the last few years. One of those is Hybrid Renewable Energy System (HRES) that planted in T. P. Rachmat Building in Bandung Institute of Technology (ITB). Problem occurred in the system is a fluctuate efficiency. The cause is a malfunction in distribute energy from energy sources to load, which cause battery to perform out of it’s allowed working range. In this project, an improvement for system efficiency has done by correction of battery working parameters and energy distribution system from sources to load. Battery working parameters included battery modul capacity and battery charged voltage. Energy distribution controlled at load limit and battery SoC. Improvement done with analyzing historical data. The purpose is to maintain a stable system efficiency at higher value and to maintain battery performance in it’s allowed working area. The result showed that load could fulfilled by battery, PV, and grid, with scheduling scenario includes lowest battery SoC value 65.0% and highest load for battery 604W. Battery tend to more balance with highest overvoltage ratio is 16.6% and highest under voltage ratio is 50.8%. Average system efficiency increased from 85.4% to 89.4% for grid mode and 85.1% to 89.3% for island mode.